Effect of heat input on temperature characteristics and fusion behavior at bonding interface of CFRTP induction welded joint with carbon fiber susceptor. Issue 3 (9th December 2022) - Wang, Feiyun; Zhang, Pingze; Luo, Jiebang; Li, Binbin; Liu, Gang; Zhan, Xiaohong
Abstract: Induction welding is a suitable and promising technique for the assembly of thermoplastic composite structural components. In this work, the simulation and experimental research of induction welding devoted to the quality and efficient bonding of carbon fiber reinforced polyetheretherketone (CF/PEEK) laminates utilizing carbon fiber susceptors is presented. The carbon fiber susceptors that consist of carbon fabric and resin film same as base materials are prepared as heating elements to concentrate the heat generation on the welding interface. A transient three‐dimensional finite element model is developed to analyze the heating characteristics and temperature distribution during the welding process. Induction welding experiments are carried out to investigate the effect of heat input on fusion behavior at the bonding interface, focusing on macro appearances, interfacial fusion morphologies and welding defects. The results show that heat distribution at the welding interface is uneven, presenting that the temperature at the edge is higher than at the center. An increase in heat input facilitates the fusion of the joints, which is demonstrated by a smaller relative width of the fusion zone and expander effective bonding area. However, macro and micro welding defects start to appear in joints due to the massive melting, ablation and thermal decomposition of resin, which are caused by excessive heat input. The micro defects dominated by pores are divided into four types according to their positions, sizes, morphologies and causes of formation. Abstract : Induction welding of CFRTP laminate